Legal Protection of Land Control of Baduy Indigenous People and Sedulur Sikep - Utomo, Laksanto; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2017)
Applicability of UUPA, a step forward in the land law, but with the foundation of land tenure and the former western lands that are not owned by an individual into a state land